Perception of information about COVID-19 and protective behaviours in relation to feelings of anxiety and happiness - Aulia Iskandarsyah; Whisnu Yudiana; Arina Shabrina; Jan Passchier (International Journal of Public Health Science (IJPHS), 2022)
This study aimed to assess the perception of the coronavirus disease 2019 (COVID-19) information provision and the health protective behavior as potential factors of feelings of anxiety and happiness among the general population in Indonesia during the outbreak. We conducted an online survey using snowball sampling techniques. The online survey collected information about demographic data, information provision of COVID-19, health prevention behaviors, and feelings of anxiety and happiness. This study involved 3,686 participants in Indonesia in the period from 2nd of April to 4th of April 2020. We found that the most frequent source of information reported was social media. The majority of participants were satisfied with the amount of information provided (98%), however 54% of the participants reported that no information or very little information about the screening/test and the treatment of COVID-19 was provided. The most frequent protective behaviour was implemented cough attitude, avoided handshake, and applied physical distancing. High exposure of Information about COVID-19 and doing preventive measures were associated with greater anxiety. Nonetheless, some preventive measures appeared to be positively associated with feelings of happiness. Our results give an indications about the information provision, application of preventive measure and the factors associated with feelings of anxiety and happiness.